Attributable risk of lung cancer deaths due to indoor radon exposure. Issue 1 (December 2016) - Kim, Si-Heon; Hwang, Won; Cho, Jeong-Sook; Kang, Dae
Abstract Exposure to radon gas is the second most common cause of lung cancer after smoking. A large number of studies have reported that exposure to indoor radon, even at low concentrations, is associated with lung cancer in the general population. This paper reviewed studies from several countries to assess the attributable risk (AR) of lung cancer death due to indoor radon exposure and the effect of radon mitigation thereon. Worldwide, 3–20 % of all lung cancer deaths are likely caused by indoor radon exposure. These values tend to be higher in countries reporting high radon concentrations, which can depend on the estimation method. The estimated number of lung cancer deaths due to radon exposure in several countries varied from 150 to 40, 477 annually. In general, the percent ARs were higher among never-smokers than among ever-smokers, whereas much more lung cancer deaths attributable to radon occurred among ever-smokers because of the higher rate of lung cancers among smokers. Regardless of smoking status, the proportion of lung cancer deaths induced by radon was slightly higher among females than males. However, after stratifying populations according to smoking status, the percent ARs were similar between genders. If all homes with radon above 100 Bq/m3 were effectively remediated, studies in Germany and Canada found that 302 and 1704 lung cancer deaths could be prevented each year, respectively. These estimates, however, are subject to varying degrees of uncertainty related to the weakness of the models used and a number of factors influencing indoor radon concentrations.